Malware mobile devices in Indonesia - Drajad, Wiryawan; Joni, Suhartono; Surjandy, .; Fernando, Yudi; Idris, Gautama So; Gui, Anderes (KnE Social Sciences, 2019)
The number of mobile devices and information technology supporting applications is currently very diverse. Ranging from expensive to cheap, even new and used. On the other hand, the increase in connections needed every year always increases along with its development. Both of these are always accompanied by increasing crime in cyberspace so that the level of risk and threats that arise will also always spread threats from time to time. Many people do not understand what cyber risk is, its impact and how minimal handling is needed to overcome the above. This research was conducted to provide an overview of cybersecurity information to anyone about the amount of malware on existing and scattered devices and the user behavior itself. It starts with scanning network traffic, type of malware, then the patterns and its characteristics. On the other hand, this also provides input on how to make minimal handling as a way to control cybersecurity. The aim of the work is to focus on establishing the basic behavior of a user on mobile malware for user profiling analysis.